Удосконалення технології вирощування квасолі з модернізацією сівалки СО-4,2 - Дриженко, Ілля Олексійович; Dryzhenko, Illia (ЦНТУ, 2024)
Робота спрямована на удосконалення технології вирощування квасолі та підвищення якості роботи овочевої сівалки СО–4,2. Проаналізовано існуючі технології вирощування квасолі. На підставі проведеного аналізу обґрунтовані удосконалення технології вирощування цієї культури з врахуванням сучасної техніки та технологій проведення операцій.В інженерній частині проведені розрахунки висівного апарата та сошників овочевої сівалки СО–4,2. Запропоновані удосконалення дозволяють збільшити продуктивність збирального агрегату та зменшити витрати палива при цьому. The work is aimed at improving the bean growing technology and improving the quality of the SO-4,2 vegetable planter. The existing technologies of growing beans are analyzed. On the basis of the conducted analysis, the improvement of the cultivation technology of this crop is substantiated, taking into account modern equipment and technologies of conducting operations. In the engineering part, the calculations of the sowing device and coulters of the SO-4,2 vegetable planter were carried out. The proposed improvements make it possible to increase the productivity of the harvesting unit and reduce fuel consumption at the same time.
Improving the technology of growing beans with the modernization of the seeder SO-4,2
Keywords: технологія вирощування; квасоля; сівалка; growing technology; beans; seeder